Novel Pathogenic Variants in a Cassette Exon of CCM2 in Patients With Cerebral Cavernous Malformations - Much, Christiane D.; Schwefel, Konrad; Skowronek, Dariush; Shoubash, Loay; von Podewils, Felix; Elbracht, Miriam; Spiegler, Stefanie; Kurth, Ingo; Flöel, Agnes; Schroeder, Henry W. S.; Felbor, Ute; Rath, Matthias (Frontiers in Neurology, 2019)
Autosomal dominant cerebral cavernous malformation (CCM) represents a genetic disorder with a high mutation detection rate given that stringent inclusion criteria are used and copy number variation analyses are part of the diagnostic workflow. Pathogenic variants in either CCM1 (KRIT1), CCM2 or CCM3 (PDCD10) can be identified in 87 to 98 % of CCM families with at least two affected patients. However, the interpretation of novel sequence variants in the 5'-region of CCM2 remains challenging as there are various alternatively spliced transcripts and different transcription start sites. Comprehensive genetic and clinical data of CCM2 patients with variants in cassette exons that are either skipped or included into alternative CCM2 transcripts in the splicing process can significantly facilitate clinical variant interpretation. We here report novel pathogenic CCM2 variants in exon 3 and the adjacent donor splice site in intron 4, describe the natural history of CCM disease in mutation carriers and provide further evidence for the classification of the amino acids encoded by the nucleotides of this cassette exon as a critical region within CCM2. Finally, we illustrate the advantage of a combined single nucleotide and copy number variation detection approach in NGS-based CCM1/CCM2/CCM3 gene panel analyses which can significantly reduce diagnostic turnaround time.